Crypto Savvy: Navigating the World of Digital Assets for Financial Gains - Rasyid, Abdul; Pertiwi, Dian; Ridhwasyah Pasolo, Muhammad (Escalate : Economics and Business Journal, 2024)
This research investigates the impact of Crypto Savvy and Digital Assets on Financial Gains through Investment Strategies at BNI Cabang Surakarta. Using a quantitative approach and structural equation modeling (SEM) with Smart PLS, data from 70 bank customers were analyzed. The results indicate significant direct effects of Crypto Savvy and Digital Assets on Investment Strategies and Financial Gains. Specifically, Crypto Savvy and Digital Assets positively influence Investment Strategies, which in turn enhances Financial Gains. Moreover, indirect effects analysis reveals that Crypto Savvy and Digital Assets indirectly contribute to Financial Gains through Investment Strategies, highlighting the mediating role of Investment Strategies in translating crypto literacy and digital asset integration into financial gains. These findings underscore the importance of enhancing knowledge and strategic management of digital assets within banking operations to optimize financial performance. The study's insights provide actionable recommendations for BNI Cabang Surakarta and similar institutions to improve their digital asset strategies and achieve sustainable financial success in the evolving financial landscape.